2021
DOI: 10.1136/bmjopen-2021-050475
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of infection and antimicrobial resistance patterns of Mycoplasma genitalium among pregnant women in the southwestern USA

Abstract: BackgroundMycoplasma genitalium is a sexually transmitted infection (STI) pathogen. There have been no published studies concerning symptomatology, prevalence data, antibiotic resistance profiling or reports of co-infection with other STI in pregnant women.ObjectiveTo describe these characteristics among pregnant women attending prenatal clinics in a large tertiary care centre.DesignRemnant genital samples collected from pregnant women between August 2018 and November 2019 were tested for M. genitalium and Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
9
1
1
Order By: Relevance
“…In the current prospective study, we found that 8% of pregnant women receiving prenatal care at OB clinics in a Southeastern US urban medical center tested positive for MG, and MG positivity was associated with younger maternal age, black race, and prior trichomoniasis. Frequency of MRMs was high (41%), which is similar to the 31% MRM frequency reported in MG‐infected pregnant women seen in Southwestern US sites 8 . The common detection of MG infection and high frequency of MRMs in this cohort underscores the great need for a better understanding of the clinical implications of untreated MG infection in pregnant women to guide screening and treatment recommendations; should treatment be necessary for MG infection in pregnant women in the United States, then additional MG treatment options that are safe in pregnancy will be needed.…”
Section: Characteristics Total (N = 224) Mg Positive (N = 18) Mg Nega...supporting
confidence: 76%
See 3 more Smart Citations
“…In the current prospective study, we found that 8% of pregnant women receiving prenatal care at OB clinics in a Southeastern US urban medical center tested positive for MG, and MG positivity was associated with younger maternal age, black race, and prior trichomoniasis. Frequency of MRMs was high (41%), which is similar to the 31% MRM frequency reported in MG‐infected pregnant women seen in Southwestern US sites 8 . The common detection of MG infection and high frequency of MRMs in this cohort underscores the great need for a better understanding of the clinical implications of untreated MG infection in pregnant women to guide screening and treatment recommendations; should treatment be necessary for MG infection in pregnant women in the United States, then additional MG treatment options that are safe in pregnancy will be needed.…”
Section: Characteristics Total (N = 224) Mg Positive (N = 18) Mg Nega...supporting
confidence: 76%
“…Routine MG screening is not currently recommended 4 because of a lack of consistent evidence of reproductive sequelae from asymptomatic infection. Most MG prevalence estimates have come from nonpregnant populations; reported prevalence in pregnant women from a small number of studies ranges from 1% to 17% 5–8 . Limited studies evaluating the association of MG with adverse pregnancy outcomes have produced conflicting results 2 .…”
Section: Characteristics Total (N = 224) Mg Positive (N = 18) Mg Nega...mentioning
confidence: 99%
See 2 more Smart Citations
“…За последние годы наблюдается снижение эффектив ности препаратов данной группы, несмотря на различия в тактике назначения в разных странах. Случаи отсут ствия положительной динамики у пациентов после ре комендованных методов лечения были описаны иссле дователями в Европе, США и странах Азии [21][22][23]. В основе этой тревожной ситуации лежит несколько при чин: отсутствие международного консенсуса в отно шении стратегии обследования и лечения пациентов, необоснованное использование макролидов при респи раторных инфекциях, плохое соблюдение схем лечения пациентами и их партнерами, недостаточная доступ ность тестов для выявления устойчивости микоплазм, а также отсутствие мониторинга за распространением штаммов, несущих маркеры резистентности к антими кробным препаратам.…”
Section: Monitoring Of Macrolide Resistanceassociated Mutations In My...unclassified